2018
DOI: 10.17219/acem/68986
|View full text |Cite
|
Sign up to set email alerts
|

Stool patterns and symptoms of disordered anorectal function in patients with inflammatory bowel diseases

Abstract: A majority of patients with IBD complain of urgency. Fecal incontinence is reported by over 50% of patients. Both worsen patients' everyday functioning. A relevant proportion of patients have symptoms consistent with constipation, which is in connection with an abnormal push/strain maneuver in more than 1/3 of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 15 publications
0
43
2
Order By: Relevance
“…Ulcerative colitis (UC) is an IBD that relapses. UC is characterized by weight loss, diarrhea, abdominal pain, and rectal bleeding (Petryszyn and Paradowski, 2018). UC affects patients’ quality of life, and UC may lead to colonic cancer if left untreated (Neurath, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is an IBD that relapses. UC is characterized by weight loss, diarrhea, abdominal pain, and rectal bleeding (Petryszyn and Paradowski, 2018). UC affects patients’ quality of life, and UC may lead to colonic cancer if left untreated (Neurath, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the burden and impact of bowel urgency as a symptom of UC have been described in multiple publications, patients with UC may be hesitant to report symptoms such as urgency due to their embarrassing nature and physicians may not ask about all symptoms [ 14 ]. ACG recently updated their clinical guidelines suggesting the inclusion of a measure of bowel urgency when assessing severity of disease activity in clinical practice, citing use of the ACG Activity Index or the Simple Clinical Colitis Activity Index [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bowel urgency is a key symptom for triggering clinical consideration of UC diagnosis and defining severity of disease activity in clinical practice [ 4 , 16 ]. Cross-sectional studies report > 80% of patients with UC experience bowel urgency [ 13 15 , 17 ], with up to half reporting having bowel urgency at least once a day [ 13 , 14 ]. While the underlying mechanism(s) resulting in bowel urgency in UC is unclear, it has been associated with chronic inflammation, which causes changes in smooth muscle tone, sensitization of intramural and increased contractile responses in the rectum, as well as the development of submucosal fibrosis [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 • Diarrheal diseases (DD): symptom of irritation, Crohn's disease, and other gastrointestinal illnesses linked to inflammation and which often display inflammatory markers. 33 • Incidents of self-harm (SH): Research has found evidence correlating chronic inflammation with extreme depressive states, measured in this case by incidents of self-harm. 5,34 The conditions for a contrast group consist of a common disease whose incidence is not directly increased by preexisting inflammatory levels that is internationally recognized and tracked across the majority of the world.…”
Section: Methodology Test Groupingmentioning
confidence: 99%